Fundamentals of well logging data interpretation for determining prospective Frasnian-Famennian Domanik deposits - D. E. Zagranovskaya; S. I. Isaeva; O. A. Zakharova (Известия высших учебных заведений: Геология и разведка)
Background. In the process of studying productive Domanik deposits of the Frasnian-Famennian, numerous uncertainties arise in identifying their effective thickness. Although several approaches have been recently proposed for identifying promising intervals in Domanik sediments, e.g. determination of the effective thickness using gas logging during geological and technical studies, the use of the interpretation method presented in the article and other methods continue to develop. Therefore, studies aimed at increasing their efficiency remain to be relevant.Aim. To develop basic methodological approaches to interpretation of well logging data with the purpose of identifying promising Domanik deposits rich in mobile hydrocarbons.Materials and methods. Geological and geophysical data obtained when investigating the wells of the according to published data of geological and geophysical resources of drilled wells in the Buzuluk depression were used to build the main well logging dependencies. In addition, the materials of core and geophysical studies of wells in the Volga-Ural oil and gas basin conducted by Gazprom Neft (PJSC) were used. Extended well logging data were collected for the wells under consideration. A number of tests and core studies, including geochemical experiments, which were carried out in deposits of Fran age, the density of resources of 5—10 samples per 1 meter of core.Results. For the first time, basic methodological approaches for identifying effective oil-saturated strata in Domanik sediments according to well logging data were developed. The developed approaches are based on the integration of geological-geophysical and geochemical data characterizing the material and mineralogical composition of rocks, the content of organic matter, the group composition of hydrocarbons and the genesis of reservoirs. In the section under study, rocks saturated with hydrocarbons were identified. The hydrocarbons were different in terms of group composition, which determined their mobility. Boundary values were obtained when interpreting data obtained by well logging methods for Domanik rocks containing mobile and stationary hydrocarbons. The proposed methodological approaches were tested on other wells in the Domanik deposits in the Orenburg region. As a result of repeated practical application and testing of the developed methodology, its effectiveness was confirmed.Conclusions. The proposed basic methodological approaches for interpretation of well logging data when identifying effective oil-saturated strata were substantiated by the geological-geophysical and geochemical properties of Domanik deposits.